Risk factors for toxoplasmosis in pregnant women in Kent, United Kingdom. - Nash, J. Q. (Cambridge University Press, 2005)
The aim of this study was to establish the relative importance of various risk factors for toxoplasmosis in a United Kingdom antenatal population. Toxoplasma immune status was determined by an immunoassay and linked to a questionnaire exploring dietary and environmental exposure to toxoplasmosis. The overall seroprevalence found was 9.1% (172/1897). A significantly higher seroprevalence was associated with rural location of the childhood home, childhood home in Europe excluding the United Kingdom, feeding a dog raw meat and increased age. A non-significant higher prevalence of toxoplasmosis was observed in women who had lived with a cat or kitten as a child. In contrast to recent European studies only weak associations between diet and toxoplasmosis were found. Gardening activity was not associated with seropositivity but a non-significant lower seroprevalence was seen in gardeners who always wore gloves. This study confirms that toxoplasma prevalence in the United Kingdom has continued to decline since the 1960s. The increasing seroprevalence with age found in this study, highlights the continuing need to educate women of childbearing age about the risk factors for toxoplasmosis.